Assessment of the individual and compounding effects of marginalization factors on injury severity, discharge location, recovery, and employment outcomes at 1 year after traumatic brain injury - Garduño-Ortega, Olga; Li, Huihui; Smith, Michelle; Yao, Lanqiu; Wilson, Judith; Zarate, Alejandro; Bushnik, Tamara (Frontiers in Neurology, 2022)
Objective: Examine the effect of eight distinct marginalized group memberships and explore their compounding effect on injury severity, recovery, discharge location, and employment outcomes 1-year after traumatic brain injury (TBI). Methods: Individuals with medically-confirmed, complicated mild-severe TBI (N=300) requiring inpatient rehabilitation care between the ages of 18-65 were recruited at two urban (public and private) health systems between 2013-2019. Data were collected from self-report and medical record abstraction. Marginalized group membership (MGM) includes racial and ethnic minority status, less than high school diploma/GED, limited English proficiency, substance abuse, homelessness, psychiatric hospitalizations, psychiatric disorders, and incarceration history. Membership in four or more of these groups signifies high-MGM. In addition, these factors were explored individually. Unadjusted and adjusted linear and logistic regressions and Kruskal Wallis tests were used to assess the associations of interest in RStudio. Results: After adjusting for age, sex, and cause of injury, compared to TBI patients with low-MGM, those with high-MGM experience significantly longer post-traumatic amnesia (95% CI = 2.70, 16.50; p=0.007) and are significantly more likely to have a severe TBI (per the Glasgow-Coma Scale) (95% CI=1.70, 6.10; p=<0.001) than a complicated mild-moderate injury. Individuals with high-MGM also are significantly less likely to be engaged in competitive paid employment one year after injury (95% CI=2.40, 23.40; p=0.001). Patients with high-MGM are less likely to be discharged to the community compared to patients with low-MGM, but this association was not significant (95% CI=0.36, 1.16; p=0.141). However, when assessing MGMs in isolation certain associations were not significant in unadjusted or adjusted models. Conclusion: This exploratory study’s findings reveal when four or more marginalization factors intersect, there is a compounding negative association with TBI severity, recovery, and employment outcomes. No significant association was found between high-MGM and discharge location. When studied separately individual MGMs had varying effects. Studying marginalization factors affecting individuals with TBI has critical clinical and social implications. These findings underline the importance of addressing multidimensional factors concurrent with TBI recovery, as the long-term effects of TBI can place additional burden on individuals and their economic stability.